The Meaning of al-Hikmah in the Tafsir of Surah Luqman Verse 12: A Comparative Analysis Study of Tafsir Nusantara by Bisri Mustafa and Quraish Shihab - Mohammad Irfan Farraz Haecal (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2023)
This research is intended to explain the interpretation of QS. Luqman verse 12 is based on a comparative analytical study of the interpretation of the archipelago by K.H. Bisri Musthofa and Quraish Shihab. This research was made using the literature study method. This is shown by the results of studies that assess that the comparison between the interpretations written by Bisri Mustofa and Quraish Shihab is quite substantial. It's just that, in its interpretation, it has some similarities in the method of interpretation and the pattern of interpretation. In addition, there are some differences in meaning in some words caused by different sources of interpretation as well as the conditions of society and the mufassir era that influence their interpretation. This can happen because the pattern of these two interpretations is adab ijtima'i (social society). The word wisdom in the verse is interpreted by two different words. In Bisri Mustofa's interpretation, it is only explained that Luqman received wisdom from God, without any clear understanding of wisdom in his view. Meanwhile, Quraish shihab defines wisdom as something that gets in the way. The point is that wisdom is something that when used can avoid and hinder the damage or ugliness that will come and will create benefits. This difference occurs because of the thinking and breadth of knowledge of the two figures in understanding the meaning of a text of verses from the Qur'an.